2013
DOI: 10.1111/jssr.12005
|View full text |Cite
|
Sign up to set email alerts
|

Social Capital, Race, and Personal Fundraising in Evangelical Outreach Ministries

Abstract: This study examines the relationship between social capital inequality, race, and personal fundraising within evangelical outreach ministries (EOMs). Drawing on quantitative and qualitative data that assess the personal fundraising experiences and outcomes of a large sample of EOM workers (N = 715), I demonstrate that the fundraising challenges and deficits faced by EOM workers are best understood as deficits in the social capital of these individual workers. Multivariate analyses affirm that social capital de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Recent studies have found differences in the demographic profile of noncongregational clergy (Perry , ; Schleifer and Cadge ) as well as the compensation processes for clergy working outside of the congregational setting (Schleifer and Chaves ). To capture any differences across occupational setting for bivocational clergy, we use the CPS industry codes.…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies have found differences in the demographic profile of noncongregational clergy (Perry , ; Schleifer and Cadge ) as well as the compensation processes for clergy working outside of the congregational setting (Schleifer and Chaves ). To capture any differences across occupational setting for bivocational clergy, we use the CPS industry codes.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, the understanding of donors and their behaviours is widely considered to be fundamental for the successful development of fundraising strategies (Webb et al ., ; Lindahl & Conley, ; Thornton, ; Perry, ), being this issue highly appraised by the pro‐social literature.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Other work by Samuel Perry (2012, 2013), along with other race and religion scholars (e.g. Cobb et al forthcoming), examines the ways race affects religious (multiracial) congregations, evangelical outreach ministries, and interracial evangelical organizations, as well as the ways religion in the United States both perpetuates and contests racial inequality.…”
Section: Shift To Overdrive: 1998 Through Todaymentioning
confidence: 99%